Red mark syndrome: Is the aquaculture water microbiome a keystone for understanding the disease aetiology? - Bruno, Antonia; Cafiso, Alessandra; Sandionigi, Anna; Galimberti, Andrea; Magnani, Davide; Manfrin, Amedeo; Petroni, Giulio; Casiraghi, Maurizio; Bazzocchi, Chiara (Frontiers in Microbiology, 2023)
Aquaculture significantly contributes to the growing worldwide food demand. However, diseases associated with intensive aquaculture conditions, especially the skin related syndromes, may have significant implications on fish health and industry. In farmed rainbow trout, red mark syndrome (RMS), which consists of multiple skin lesions, currently lack recognized aetiological agents, and increased efforts are needed to elucidate the onset of these conditions. Most of the past efforts were focused on analysing skin lesions, but no study focused on water, a medium constantly interacting with fish. Indeed, water tanks are environmental niches colonised by microbial communities, which may be implicated in the onset of the disease. Here, we present the results of water and sediment microbiome analyses performed in an RMS-affected aquaculture facility, bringing new knowledge about the environmental microbiomes harboured under these conditions. No significant differences in the bacterial community structure on the whole were reported in RMS-affected tanks compared to the healthy ones, but we highlighted significant differences in microbiome composition when analysing different samples sources (i.e. water and sediments). However, looking at the finer scale, we measured significant changes in the relative abundances of specific taxa in RMS-affected tanks, especially when analysing water samples. Our results provide worthwhile insight into a mostly uncharacterized ecological scenario, aiding future studies on the aquaculture built environment for disease prevention and monitoring.